Toolkit to combat trafficking in persons. (United Nations Office on Drugs and Crime, 2006)
The United Nations Office on Drugs and Crime launched a toolkit to help Governments, policy-makers, law enforcement agencies and NGOs tackle human trafficking more effectively. It contains practical tools for police and other law enforcement officers such as a checklist to help identify trafficking victims as well guidance on interviewing victims and victim protection. The toolkit also outlines key aspects of a comprehensive response to human trafficking, such as the need to bring national legislation into line with international standards and strengthen international cooperation in criminal justice, including the extradition of criminals, seizure of assets and confiscation of the proceeds of crime.